Complications After Pediatric Hip Fractures: Evaluation and Management. Issue 1 (1st January 2020) - Lark, Robert K.; Dial, Brian L.; Alman, Benjamin A.
Abstract : Pediatric proximal femur fractures are high-energy injuries with predictable and morbid complications. Osteonecrosis of the femoral head is the most common complication with identified risk factors including fracture type, patient's age, degree of displacement, timing to reduction, and stability of fixation. Additional complications include nonunion, coxa vara, and premature physeal arrest. The mainstay of treatment for traumatic pediatric osteonecrosis is hip preservation with total hip arthroplasty being reserved as a salvage procedure. An anatomic fracture reduction and a biomechanically stable construct are critical to prevent both nonunion and osteonecrosis. This review will look at the individual surgical interventions for the management of the associated complications of pediatric proximal femur fractures.